ЧОВЕК С МАНСАРДЕ МОМЧИЛА МИЛАНКОВА ИЛИ СЛИКА СТВАРНОСТИ У РОМАНУ КЛУПА НА КРАЈУ СВЕТА (Philological Studies, 2019)
This paper attempts to focus more attention on the importance of Momčilo Milankov’s novel Klupa na kraju sveta (The Bench at the End of the World, 1964), which highlights the author’s skill in construing a fictional world on the basis of aesthetic, cultural and reality phenomena of the time of its creation: on one hand, Nouveau Roman, Film noir, the Yugoslav Black Wave films, trivial literature – pulp crime fiction, Yugoslav Socialist reality of the nineteen-sixties, and on the other hand – classical artistic achievements, from Dostoyevsky’s Crime and Punishment to Hitchcock’s films and, at least partially, Aldous Huxley’s Point Counter Point and existentialist philosophy and literature. According to that, Milankov’s man from the garret in Klupa na kraju sveta appears not as a product of modern urban alienation and the personal insignificance and impersonality of the small bureaucrat (as the critics usually interpreted him), but as a result of the writer’s intention to create, Hitchcock-like, a psychologically convincing portrait of a impassioned reader of crime fiction who turns into their accidental victim. Apart from that, we tried to demonstrate how much the world image in the novel is devoted to a criticism of Socialist reality of the nineteen-sixties, similar to the one personified in the films of the Yugoslav Black Wave. By choosing the semantics of possible worlds as a starting point, we pointed out the polyphone structure of this novel, a hybrid that unites the crime genre with social, psychological and existentialist themes and motifs.
Keywords: Momčilo Milankov, Klupa na kraju sveta (The Bench at the End of the World), Nouveau Roman, Film noir, Yugoslav Black Wave, pulp crime fiction, criticism of reality, the semantic of possible worlds